2009
DOI: 10.1245/s10434-009-0693-0
|View full text |Cite
|
Sign up to set email alerts
|

Should Hepatic Metastatic Colorectal Cancer Patients with Extrahepatic Disease Undergo Liver Resection/Ablation?

Abstract: A thorough understanding of the biology of disease and appropriate multimodality care can lead to improved survival in patients with EHD, when compared with chemotherapy alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 14 publications
1
21
0
1
Order By: Relevance
“…Without treatment, median overall survival for patients with CRLM is 8 months [1]; this prognosis worsens where there is both liver and extrahepatic disease (EHD). Current chemotherapeutic regimens can prolong survival in patients with CRLM and EHD to 26.5 months, but best evidence dictates superior outcomes if surgical resection is performed [2-5]. Extension of hepatic metastatic disease to involve adjacent viscera was traditionally a contraindication to resectability.…”
Section: Introductionmentioning
confidence: 99%
“…Without treatment, median overall survival for patients with CRLM is 8 months [1]; this prognosis worsens where there is both liver and extrahepatic disease (EHD). Current chemotherapeutic regimens can prolong survival in patients with CRLM and EHD to 26.5 months, but best evidence dictates superior outcomes if surgical resection is performed [2-5]. Extension of hepatic metastatic disease to involve adjacent viscera was traditionally a contraindication to resectability.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, some authors reported favorable survival results in selected patients with CHEHMs, in which complete resection of all metastatic disease (8)(9)(10)(11) could be performed. Currently, several centers consider that the presence of CEMs is no longer an absolute contraindication to liver resection (if complete resection of hepatic and extrahepatic disease can be performed), extrahepatic disease representing only a poor prognostic factor for patients with CHMs.…”
Section: Introductionmentioning
confidence: 99%
“…Although the role of surgery in presence of multiple sites of MCC is almost un-explored, the combined and/ or sequential resection of liver, lymph nodes, lung metastases in various combinations has been tested with encouraging outcomes in very selected cases [11] . Radical surgery for concomitant liver and extra-hepatic MCC has shown results that seem comparable to those obtained for isolated hepatic metastases [12][13][14][15] . For colorectal liver metastases (LM), radical surgery offers a chance of cure in at least 17% of patients and liver resection (LR) has become the standard treatment for patients with resectable disease [16] .…”
Section: Introductionmentioning
confidence: 67%